2016
DOI: 10.1016/j.ijnurstu.2015.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare providers’ knowledge, attitudes and practices towards medical male circumcision and their understandings of its partial efficacy in HIV prevention: Qualitative research in KwaZulu-Natal, South Africa

Abstract: Background Medical male circumcision has been shown to reduce HIV transmission to an uninfected male partner. In South Africa, medical male circumcision programs were rolled-out in 2010. Objectives Prior to roll-out, we explored healthcare providers’ knowledge, attitudes and practices about medical male circumcision and their understandings of partial efficacy for HIV prevention. Design We conducted qualitative research, using in-depth interviews. Setting Participants were from three rural and three urba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
(40 reference statements)
0
8
0
Order By: Relevance
“…Third, HCWs shared substantial misgivings about the promotion of partially efficacious NPTs; yet, their support is crucial to the dissemination of these products (Milford et al., 2016 ). Addressing concerns that partially effective NPTs may encourage risk compensation behaviour or that NPTs may specifically discourage condom use is paramount, particularly in the face of competing evidence in regard to actual risk compensation behaviour (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Third, HCWs shared substantial misgivings about the promotion of partially efficacious NPTs; yet, their support is crucial to the dissemination of these products (Milford et al., 2016 ). Addressing concerns that partially effective NPTs may encourage risk compensation behaviour or that NPTs may specifically discourage condom use is paramount, particularly in the face of competing evidence in regard to actual risk compensation behaviour (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of ‘partial efficacy’ is complex and may be difficult to explain (Layer, Beckham, Momburi, & Kennedy, 2013 ; Newman, Duan, Rudy, Roberts, & Swendeman, 2004 ; Underhill et al., 2016 ); even health care providers report erroneous understandings (Milford et al., 2016 ). Yet it is essential for individuals using NPTs to understand that these products are only partially efficacious.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data on the perceptions of VMMC currently appears to be limited to the perceptions of pharmacy and nursing students (13). Research on health care workers' attitudes and understanding of VMMC emanates from a time prior to the roll-out of VMMC in South Africa (14), while current data on health care workers' attitudes and perceptions of implementing VMMC are limited to two regions in Africa, both of which are urban settings (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…Providers’ knowledge of both didactic material and practical skills is highly variable . A South African study found that most providers knew that circumcision significantly reduced the risk of HIV acquisition in men, but most did not have the knowledge to communicate this to clients . Common provider training deficiencies included screening for contraindications, provision of effective analgesia, and managing AEs .…”
Section: Introductionmentioning
confidence: 99%